2014
DOI: 10.1614/wt-d-13-00051.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Economics of a Rotating Cultivator in Bok Choy, Celery, Lettuce, and Radicchio

Abstract: A commercial intrarow rotating cultivator was tested for weed removal and impact on hand-weeding times in bok choy, celery, lettuce, and radicchio. The rotating cultivator was tested as an automated crop thinner and weeder in direct-seeded bok choy and lettuce as an alternative to hand-thinning and -weeding. The rotating cultivator utilized machine-vision guidance to align a rotating disk with the crop plant to be saved and to remove weeds and undesired crop plants. The rotating cultivator was compared to a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 15 publications
0
41
0
1
Order By: Relevance
“…All ten of the automation studies identified scenarios in which automation was economically beneficial. Of the ten studies, Fennimore et al (2014) were most sceptical about the benefits. They stated that with the technology available at that time, machine vision-guided weeding with a rotating cultivator between plants was economically feasible for transplanted vegetables, but not for the direct seeded crops on which field trials had been conducted.…”
Section: Automated But Not Autonomousmentioning
confidence: 99%
“…All ten of the automation studies identified scenarios in which automation was economically beneficial. Of the ten studies, Fennimore et al (2014) were most sceptical about the benefits. They stated that with the technology available at that time, machine vision-guided weeding with a rotating cultivator between plants was economically feasible for transplanted vegetables, but not for the direct seeded crops on which field trials had been conducted.…”
Section: Automated But Not Autonomousmentioning
confidence: 99%
“…Advanced smart-machine technology for automatic weed control has been demonstrated in certain row crops when weed density is low; however, the proportion of weeds controlled automatically is still well below 100%, and commercial-scale applicability to all crops, weed species, and growing conditions has yet to be demonstrated (e.g., Fennimore et al 2014). Currently, the most critical technological bottleneck preventing the realization of fully automatic weed control machines is the lack of a robust weed sensor that can detect and distinguish among closely related crop and weed species at rates well above 95% in the field environment.…”
Section: Co-robotics the Symbiosis Among Man Machine And Crop Plantsmentioning
confidence: 99%
“…A automatização do controle das plantas daninhas apresenta dois aspectos-chave, a detecção de culturas/plantas daninhas e os sistemas de controle das plantas daninhas. A detecção automática permite que máquinas comerciais reconheçam padrões de linhas de culturas e controlem dispositivos automatizados que executam o controle das plantas daninhas nas entrelinhas sem reduzir o estande da cultura ou ralear a linha de semeadura da cultura (Ascard e Fogelberg, 2008;Fennimore et al, 2014).…”
Section: Controle Mecânico Automatizadounclassified